Coastal Community Perception of the Bahavior of Throwing Garbage into The Sea in North Mangga Dua Subdistrict South Ternate City - Namira Ismail; Nadias Humairah Mustafa (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study explores coastal community perceptions of waste disposal behavior into the sea in North Mangga Dua Village, South Ternate City. Using a qualitative phenomenological approach, data were collected through in-depth interviews, observations, and documentation involving community leaders, fishermen, and coastal residents. Data were analyzed using thematic analysis. The findings identified four main themes: the perception of the sea as a natural dumping site, low environmental awareness, cognitive dissonance, and limitations in waste management systems. Many residents believe that ocean currents can naturally remove waste, making sea disposal a common practice passed down through generations. Although some community members understand the environmental impacts of marine pollution, they continue the behavior due to convenience and social habits. Inadequate waste management facilities, including limited waste bins and ineffective waste collection services, further contribute to the problem. The study concludes that social habits, environmental awareness, and insufficient waste management infrastructure significantly influence waste disposal behavior among coastal communities. Strengthening environmental education and improving waste management facilities are essential to reducing marine pollution in coastal areas.